2022
DOI: 10.4103/jfmpc.jfmpc_2029_21
|View full text |Cite
|
Sign up to set email alerts
|

Parental knowledge of children’s developmental milestones in Aseer, Saudi Arabia

Abstract: Background: Better parental knowledge about developmental milestones of children is linked to better parent–child interaction. Only a handful of surveys have been conducted to evaluate parental knowledge of developme ntal milestones in Arabic-speaking countries. Materials and Methods: The study is a cross-sectional, questionnaire-based observational investigation using a simple random sampling scheme. The sampling frame consisted of all parents attending the family medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
1
2
Order By: Relevance
“…Only, 14 percent of our respondents answered correctly. In one of the studies done in Aseer, Saudi Arabia shows that only 12.5%, slightly higher than our population [ 17 ]. This shows that overall knowledge regarding social milestones is poor regardless of the region of the world.…”
Section: Discussioncontrasting
confidence: 60%
“…Only, 14 percent of our respondents answered correctly. In one of the studies done in Aseer, Saudi Arabia shows that only 12.5%, slightly higher than our population [ 17 ]. This shows that overall knowledge regarding social milestones is poor regardless of the region of the world.…”
Section: Discussioncontrasting
confidence: 60%
“…Only, 14 percent of our respondents answered correctly. In one of the studies done in Aseer, Saudi Arabia shows that only 12.5%, slightly higher than our population (11). This shows that overall knowledge regarding social milestones is poor regardless of the region of the world.…”
Section: Knowledge Related To Different Parameters Of Developmental D...contrasting
confidence: 56%
“…Although Saudi parents essentially placed confidence in pediatric roles for milestone guidance, only around half regarded current physician information as entirely satisfactory for establishing adequate developmental consciousness [ 9 ]. Previous evidence indicates that nearly 60% of parents show a willingness for more excellent information from healthcare providers [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that only 29 (7.7%) participants had outstanding knowledge, while 141 (37.6%) participants had poor knowledge. Additionally, 180 (48%) participants had a sufficient degree of knowledge [ 9 ]. Furthermore, a cross-sectional study conducted in the Eastern Province of Saudi Arabia from January to February 2020 revealed that only 51.8% of participants were aware of developmental milestones.…”
Section: Introductionmentioning
confidence: 99%